Linewidth analysis of image potential states on noble metal surfaces with high‐energy resolved two‐photon photoemission spectroscopy. (27th July 2016) - Nakazawa, Takeo; Arafune, Ryuichi; Takagi, Noriaki; Kawai, Maki
Abstract : Electron dynamics in the excited states are governed by inelastic and quasielastic scattering processes. It is required to determine both scattering rates for complete understanding of the electron dynamics. Although time‐resolved two‐photon photoemission (2PPE) spectroscopy is a unique and powerful tool to measure the scattering rates directly, it is not easy to evaluate the quasielastic scattering rate. Precise measurement of spectral linewidth with high‐energy resolution is an alternative way to determine the elastic scattering rate. The high energy‐resolution 2PPE measurement has not been well developed because of the tradeoff between the time and the energy resolutions. In this study, we have succeeded in improving the energy resolution of 2PPE by using picosecond laser pulses. We have measured the 2PPE spectra of image potential states (IPSs) on Cu(001) and n = 1 IPS on Au(001) and discussed the dynamics of the electrons excited into the IPS on both surfaces from the linewidth analysis. Copyright © 2016 John Wiley & Sons, Ltd.